2010
DOI: 10.1021/pr100412w
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Distinct Portal Vein Tumor Thrombi in Hepatocellular Carcinoma Patients

Abstract: Portal vein tumor thrombosis (PVTT) in patients with hepatocellular carcinoma (HCC) is known as a major complication associated with poor survival. We clinically defined a type of distinct PVTT (dPVTT) in small HCC patients that is distant to liver parenchyma tumor (PT). The biological features of dPVTT are not clear. We utilized two-dimensional electrophoresis and tandem MS to compare and identify differentially expressed proteins between dPVTT and PT tissues. Of the 65 spots identified as differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…XAGE-1b was shown to be a risk factor affecting PVTT, TNM staging and the 1-year recurrence. PVTT in HCC patients is a well-known major complication that is correlated with a poor prognosis (22). The patients with PVTT or higher TNM stages (II~IV) were found to be more likely to have increased XAGE-1b mRNA levels.…”
Section: Discussionmentioning
confidence: 93%
“…XAGE-1b was shown to be a risk factor affecting PVTT, TNM staging and the 1-year recurrence. PVTT in HCC patients is a well-known major complication that is correlated with a poor prognosis (22). The patients with PVTT or higher TNM stages (II~IV) were found to be more likely to have increased XAGE-1b mRNA levels.…”
Section: Discussionmentioning
confidence: 93%
“…As the majority of PVTT emerges around the primary tumor (aPVTT), the traditional belief is that PVTT develops following the direct invasion of a liver tumor, resulting in a hepatic artery-portal vein fistula and portal vein countercurrent. However, we detected distinct PVTT (dPVTT), a unique type of PVTT distant from the liver tumor nodule 16 . Comparative proteomics showed that dPVTT possessed molecular signatures different from those of liver tumors, implying that the mechanism of PVTT formation is far more complicated than previously thought.…”
Section: Mechanisms Of Pvtt Formationmentioning
confidence: 85%
“…It is likely that Annexin A5 has a very short unphosphorylated N-terminus compared with other Annexins, contributing to a series of functions, such as cell proliferation and invasion (6,10), signal transduction (11,12), and anticoagulation (13). Previous studies have reported that Annexin A5 promoted tumorigenesis and progression in a variety of cancers, including hepatocarcinoma, colorectal cancer and breast cancer (14,15). However, the possible relationship between Annexin A5 and RCC is not clear.…”
Section: Introductionmentioning
confidence: 99%